EMPLOYEE WELLNESS PROGRAMMES FOR IMPROVED PERFORMANCE - Shikha Vyas-Doorgapersad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Humans are compelled to work to have financial security, as well as to achieve purpose, fulfillment, and connections with other workers who realize lower-level workplace requirements like peer group affiliation, peer approval, and interpersonal engagement. Due to the rigorous nature of the office, there are several elements, like stress, covid-19, work pressure, etc., that may interfere with relationships, teamwork, and alliances between people. Employees may experience mental, emotional, and psychological problems because of this condition, which causes emotional stress that has an impact on their general health. These factors are incorporated into workplace employee wellness programmes (EWPs) as part of human resource management. Additionally, the EWP is linked to Sustainable Development Goal (SDG) 3, which calls for improved health and wellness. The article's goal is to examine obstacles to SDG 3 implementation and offer various organizational measures that must be put in place to guarantee workplace wellbeing for employees. The qualitative research methodology is used to gather pertinent data. The findings demonstrate that the successful implementation of EWP may help both employers and employees manage wellness to maintain levels of employee performance and, consequently, organizational productivity. The study offers policy recommendations considering the need for organizations and employees, both individually and collectively, to find ways to look after their health (physical wellness), behaviour (emotional and psychological wellness), and remain connected to themselves and the world. The study also offers ways to de-stress through exercise, yoga, prayer, meditation, online help groups, virtual consultations, etc. incorporating spiritual wellness.